Diet-related greenhouse gas emissions and major food contributors among Japanese adults: comparison of different calculation methods. Issue 5 (11th April 2021) - Sugimoto, Minami; Murakami, Kentaro; Asakura, Keiko; Masayasu, Shizuko; Sasaki, Satoshi
Abstract: Objective: To develop a greenhouse gas emissions (GHGE) database for Japanese foods using three different approaches, compare the results of estimated diet-related GHGE and determine major food contributors among Japanese adults. Design: Cross-sectional. Three GHGE databases were developed: (1) a literature-based method including a literature review of life cycle assessment studies of Japanese foods and (2) production- and (3) consumption-based input–output tables (IOT)-applied methods using the Japanese IOT. All databases were linked to the Japanese food composition table and food consumption data. Diet-related GHGE was estimated based on each database and the 4-d dietary record data. Diet-related GHGE were compared in both total and food group level between the databases. Setting: Japan. Participants: 392 healthy adults aged 20–69 years. Results: The mean diet-related GHGE significantly differed according to the calculation methods: 4145 g CO2 -equivalent (CO2 -eq)/d by the literature-based method, 4031 g CO2 -eq/d by the production-based method and 7392 g CO2 -eq/d by the consumption-based IOT-applied methods. It significantly differed in food group level as well. Spearman's correlation coefficients between three methods ranged from 0·82 to 0·86. Irrespective of the methods, the top contributor to GHGE was meat (19·7–28·8 %) followed by fish and seafood (13·8–18·3 %). Conclusions: Although the identified major food contributors to GHGE were comparable between the three methods, the estimated GHGE values significantly differed by calculation methods. This finding suggested that caution must be taken when interpreting the estimated diet-related GHGE values obtained using the different calculation methods of GHGE.